The Implementation of Child Livelihood Payment after Divorce Occurs in the Perspective of the Shafi` School of Fiqh and Positive Law (Post-Court Judgment Analysis Study in North Sumatra) - Asmuni Asmuni; Pagar Hasibuan; Ahmad Zuhri Rangkuti (Budapest International Research and Critics University, 2021)
As many as 80% of the judges' verdicts at the North Sumatra Religious Court (PA Sumut) were ignored by their former husbands, excluding education and health costs. This study aims: (1) to find out how to pay for children's livelihoods after divorce, from the perspective of the Syāfi`ī school of jurisprudence, (2) to find out how to pay for child support after divorce, with a positive legal perspective (3) to find out how to determine children's livelihoods after divorce from the perspective of the fiqh school of thought Shafi`ī PA North Sumatra. This research uses field research methods by collecting primary data with direct interview respondents, direct observation in North Sumatra PA, collecting closely related data and information, supported by library research methods. This type of research is field research. This research approach is sociological juridical. The nature of the research is descriptive-analysis. The data sources were obtained from primary, secondary and tertiary legal materials. Data collection methods by means of interviews and documentation. Research conclusions: (1) how to pay for child support after divorce from the perspective of the Syāfi`ī school of jurisprudence, namely a) asking or taking the method directly according to the local urf, b) giving it directly by the ex-husband or through a representative according to the local urf, c) filing a lawsuit. (2) The method of paying for children's livelihoods after divorce from a positive legal perspective, namely: a), handing over directly to the mother, b) the Court's decision due to divorce or sue (3) The way North Sumatra PA determines children's livelihoods after divorce, namely through: a) the child's mother, b) a verdict, c) filing a lawsuit.